Terri Hron (Canadian New Music Network) - Jakobsson, Anna (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

David Denada - Farnsworth, Brandon (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Myriam Boucher + Followup - Boucher, Myriam (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)
The caesura in musical production caused by recent global lockdowns has made contemporary music’s crisis of societal relevancy more apparent than ever. Bringing together interviews with music curators, musicians, activist networks and institutional leaders, this book details existing practices and approaches, showing that change is possible but only if the recent wave of interest in curatorial practices, diversity and divestment from a white, European bourgeois aesthetic are taken seriously by the musical establishment. This expanded second edition of Taking the Temperature adds a new preface, five new interviews, as well as followups with previous interviewees. Radiating out from the Ultima Festival and Oslo, ..

Barbara Scales - Farnsworth, Brandon; Massera, Vanessa (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)